Analisis Praktik Pertanian yang Baik dan Pendapatan Usahatani Kelapa Dalam di Kabupaten Indragiri Hilir - Nahdiani, Hindun; Bakce, Djaimi; Hadi, Syaiful (Universitas Medan Area, 2024)
Coconut cultivation in Indragiri Hilir Regency has been a hereditary tradition. However, in recent years, a decrease in land area and production volume has resulted in a decline in farmers' income. This study aims to evaluate current coconut cultivation practices and calculate the income from coconut farming in Indragiri Hilir. The analysis methods used are gap analysis and income analysis. For sampling, a non-probability sampling method was employed. The results show that most farmers have implemented recommended cultivation practices; however, aspects such as planting distance, fertilizer dosage, and pest and disease control are not optimal. This has led to low coconut production and a decrease in coconut selling prices. Additionally, the income from coconut farming per hectare per year in Indragiri Hilir Regency is IDR 2,065,936/Ha/year, indicating that the income of coconut farmers remains low. To address these issues, comprehensive efforts from the local government are needed, such as intensive training for farmers on standard cultivation practices, as well as subsidies for fertilizers and herbicides. These steps are expected to enhance farmers' skills in managing coconut plantations, thereby significantly increasing production and income. Thus, it is hoped that the problem of low farmer income in Indragiri Hilir can be minimized, and this sector can make a greater contribution to the local economy.